Counseling on Clean and Healthy Behavior (PHBS) for High School Students - Nur Rizkiyah (PT FORMOSA CENDEKIA GLOBAL, 2023)
This activity aims to provide knowledge to students about the importance of a healthy lifestyle from an early age. This counseling is carried out to provide knowledge on how to live a healthy lifestyle and prevent some dangerous diseases such as diabetes, heart disease and high cholesterol. This activity uses interactive counseling methods to students. Students who participated in this activity were 87 students of class X SMA Yadika. PHBS knowledge test results reached 70.5 which means quite good. These results still require follow-up counseling related to such as a healthy environment and nutritious and healthy food and a good diet.